PERBANDINGAN PEMBELAJARAN BERBASIS PROYEK DENGAN BERBASIS MASALAH DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH - Muhammad Irfan Rumasoreng; Nanang Khuzaini; Ani Yuli Astuti (Academy of Education Journal, 2020)
This research aims to: investigate in more effective between project based learning and problem based learning in terms of problem solving skills of students on the 7th grade. The research is a quasi experiment research with pre-test and post-test of non-equivalent control grup design. This study used two experimental groups. The population include all 7th grade students of SMP N 2 Nanggulan which consist of three classes. From the population, the two classes which were class VII B and class VII C is randomly as research sample. Matematics teaching in class VII B used the problem based learning and class VII C used the project based learning. The result show that: project based learning and problem based learning there has significant difference effective in terms of problem solving skills of students on the 7th grade.